Improving Student Learning Outcomes through the Application of Problem-Based Learning Methods at SMK Negeri 1 Syamtalira Aceh Utara - Nasrizal; Ridwan; Rusna (Jurnal Profesi Guru Indonesia, 2024)
This research aims to improve student learning outcomes in Islamic religious education learning using problem-based learning. This research is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subject of this study is vocational high school students. The data of this study was obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze the learning activities of teachers and students. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with research success indicators. The results of the study show that problem-based learning can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completeness in each cycle with details of the pre-cycle of 42.19%, the first cycle of 69.57% and in the second cycle it increased to 87.93%. Thus, the use of problem-based learning can be used as an alternative to improve student learning outcomes in Islamic religious education learning.